2022
DOI: 10.3390/ijms231911877
|View full text |Cite
|
Sign up to set email alerts
|

FoxO Transcription Factors: Applicability as a Novel Immune Cell Regulators and Therapeutic Targets in Oxidative Stress-Related Diseases

Abstract: Forkhead box O transcription factors (FoxOs) play an important role in maintaining normal cell physiology by regulating survival, apoptosis, autophagy, oxidative stress, the development and maturation of T and B lymphocytes, and the secretion of inflammatory cytokines. Cell types whose functions are regulated by FoxOs include keratinocytes, mucosal dermis, neutrophils, macrophages, dendritic cells, tumor-infiltrating activated regulatory T (Tregs) cells, B cells, and natural killer (NK) cells. FoxOs plays a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 123 publications
0
9
0
Order By: Relevance
“…These substrates are involved in various cellular processes, such as glucose metabolism, lipid metabolism, oxidative stress, cell cycle arrest, and apoptosis. FOXO1 has been implicated (37)(38)(39)(40) in the pathogenesis and prevention of various diseases, such as diabetes, obesity, cardiovascular diseases, neurodegenerative diseases, and cancers. For example, FOXO1 can improve insulin sensitivity and glucose homeostasis by regulating gluconeogenic enzymes, and GLUT4 expression can inhibit adipogenesis and lipogenesis by suppressing PPARγ and SREBP-1c expression.…”
Section: Resultsmentioning
confidence: 99%
“…These substrates are involved in various cellular processes, such as glucose metabolism, lipid metabolism, oxidative stress, cell cycle arrest, and apoptosis. FOXO1 has been implicated (37)(38)(39)(40) in the pathogenesis and prevention of various diseases, such as diabetes, obesity, cardiovascular diseases, neurodegenerative diseases, and cancers. For example, FOXO1 can improve insulin sensitivity and glucose homeostasis by regulating gluconeogenic enzymes, and GLUT4 expression can inhibit adipogenesis and lipogenesis by suppressing PPARγ and SREBP-1c expression.…”
Section: Resultsmentioning
confidence: 99%
“…These substrates are involved in various cellular processes, such as glucose metabolism, lipid metabolism, oxidative stress, cell cycle arrest, and apoptosis. FOXO1 has been implicated (37)(38)(39)(40) in the pathogenesis and prevention of various diseases, such as diabetes, obesity, cardiovascular diseases, neurodegenerative diseases, and cancers. For example, FOXO1 can improve insulin sensitivity and glucose homeostasis by regulating gluconeogenic enzymes, and GLUT4 expression can inhibit adipogenesis and lipogenesis by suppressing PPARγ and SREBP-1c expression.…”
Section: Resultsmentioning
confidence: 99%
“…FOXO3A is a core regulator involved in the modulation of various physiological and pathological processes, including oxidative stress, proliferation, differentiation, apoptosis, and metabolism. 24 It has been reported that decreased FOXO3A expression was associated with enhanced cardiac fibrosis in peripartum cardiomyopathy, which is closely related to the promoting antioxidative defense function of FOXO3A. 25 Additionally, FOXO3A also has a role in inhibiting cardiac fibroblast hyperplasia by promoting p27 expression.…”
Section: Discussionmentioning
confidence: 99%